Study of androgen and atherosclerosis in old-age male - 杨云梅 吕雪英 黄卫东 徐哲荣 吴灵娇 (Journal of Zhejiang University. B. Science, 2005)
Objective： To observe the difference of androgen and inflammatory cytokines level in atherosclerosis and analyse their relations. Method： Both carotid arteries and arteries of lower extremity were subjected to ultrasonic examination by Doppier＇s method. Those with much atheromatous plaque formation were ranged into case group, and those with normal result formed control group. Total, free testosterone and estradiol were assayed by radioimmunoassay. C reactive protein （CRP） was assayed by nepheloturbidity. Tumor necrosis factor-α（TNF-α）, lnterleukin-6 （IL-6）, lnterleukin-8 （IL-8）, lnterleukin-10 （IL-10）, Interleukin-18 （IL-18）, soluble intercellular adhesion molecule-1 （sICAM-1） and soluble vascular cell adhesion molecule-1 （sVCAM-1） were assayed by ELISA. The mean difference between two groups and the correlation between free testosterone and cytokines were analysed. Results： Free testosterone was （6.337±3.371） pg/L in case group and （11.375±4.733）pg/L in control group, P〈0.01. No differences were found in total testosterone and estradiol. CRP was （27.294±10.238）mg/L in case group and （12.843±6.318） mg/L in control group, P〈0.01. IL-6 was （41.700±31.385）pg/L in case group and （25.396±20.772）pg/L in control group, P〈0.05. IL-8 was （89.249±58.357）pg/L in case group and （67.873±31.227）pg/L in control group, P〈0.05. sICAM-1 was （470.491±134.078）pg/L in case group and （368.487±97.183）pg/L in control group, P〈0.01. sVCAM-1 was （537.808±213.172）pg/L in case group and （457.275±157.273）pg/L in control group, P〈0.05. There were no differences in TNF-α, IL-10 and IL-18. Correlation analysis showed that FT （free testosterone） had negative correlation with CRP, IL-6 and sICAM-1. Among them FT had well correlation with CRP, correlation index was -0.678. Conclusion： Free testosterone was in negative correlation with atherosclerosis in old-age male. Free testosterone may have the role of anti-atherosclerosis, and this effect was not achieved by its transformation to estradiol. Low tree testosterone level was followed by increased level of inflammatory cytokines. Low free testosterones coexist with inflammation and they both affect the process of atherosclerosis in old-age male.